Investigation of marble limestone biocolonization: the case study of Convento das Maltezes in Estremoz - Bhattacharya, Sriradha (2020)
Over centuries, different lithotypes – either calcitic such as limestones and marbles, and/or silicious such as sandstones and granites have been used in historical monuments, whose deterioration/degradation differs as per the hardness, porosity and chemical composition of each stone. However, over the last decades living microorganisms have been associated with structural and aesthetical damages to building stone in historical monuments. The current research focuses on the investigation of degradation/deterioration in architectural marble monuments, with the aim to contribute to a better understanding the role of microbial agents on the biodegradation/biodeterioration of monuments built in marble. A multidisciplinary approach was employed to perform material characterisation and alteration products detection involving in situ and laboratory analysis in order to arrive at a comprehensive assessment of biocolonisation. Studying the microbial proliferation gave a wider perspective on recognising the role of microorganisms and their ability to degrade cultural heritage materials, which in turn helps understand and chalk out a mitigation process for future. The micro-analytical techniques distinguished and identified the alterations processes like patina formation, pigmentation and biofilms formation. The biocontamination was characterised by SEM-EDS, culture-dependent methods (CDM) and Next Generation Sequencing (NGS). CDM and NGS confirm the presence of several strains of bacteria, filamentous fungi and yeasts that appears to contribute to the presence of calcium oxalates, carotenoids and biofilms formation. Thus, it is imperative to study and comprehend the causes for marble degradation/deterioration, and recognise the source for the alteration of these materials, in order to define effective strategies to prevent marble decay and safeguard our cultural heritage; RESUMO: Biocolonização de pedra calcária: O caso de estudo do Convento das Maltesas em Estremoz Ao longo dos séculos, diferentes litotipos - calcíticos, como calcários e mármores, e / ou siliciosos como arenitos e granitos - têm sido utilizados em monumentos históricos, cuja degradação/deterioração difere de acordo com a dureza, porosidade e composição química de cada pedra. Nas últimas décadas, a presença de microrganismos tem sido associada a danos estruturais e estéticos de pedra utilizada em monumentos históricos. O presente trabalho tem como objetivo o estudo da degradação/deterioração de mármore aplicado em património arquitetónico, com o objetivo de contribuir para uma melhor compreensão do papel dos agentes microbianos na biodegradação/biodeterioração deste material, em contexto histórico. Foi utilizada uma abordagem multidisciplinar na caracterização de materiais e na deteção de produtos de alteração, envolvendo análises in situ e em laboratório, no sentido de obter uma avaliação abrangente da biocolonização. O estudo da proliferação microbiana permite uma perspetiva mais ampla no reconhecimento do papel dos microrganismos e da sua capacidade para degradar os materiais do património cultural, o que, por sua vez pode vir a ser útil na definição de estratégias de mitigação, para o futuro. As técnicas microanalíticas permitiram distinguir e identificar alguns processos de alteração, como formação de pátinas, pigmentação e formação de biofilmes. A biocontaminação foi caracterizada por SEM-EDS, através de métodos dependentes de cultura (CDM) e por Sequenciação de Nova Geração (NGS). CDM e NGS confirmam a presença de várias espécies de bactérias, fungos filamentosos e leveduras que parecem contribuir para a presença de oxalatos de cálcio, formação de carotenóides e de biofilmes. Assim , é imperativo estudar e compreender as causas da degradação/deterioração do mármore, e reconhecer os agentes responsáveis pela alteração destes materiais, de forma a que possam ser definidas estratégias eficientes para prevenção do seu declínio, contribuindo para a salvaguarda dos nossos bens patrimoniais.